Using cloud technologies in modern distance learning systems - A. B. Andrukhovskyi (CTE Workshop Proceedings, 2013)
Modern society with its constant development, gravitation to the processes of globalization requires an increase in the level of automation of all information processes, including in the field of education. Over the past few years we have seen a growing interest of scientists and IT specialists in the Software as a Service model. SaaS should be considered a particular case of the more general service-oriented software architecture, which actually defines that software components act as common services and can be used independently or recombined in other programs.